2018
DOI: 10.1073/pnas.1717092115
|View full text |Cite
|
Sign up to set email alerts
|

Training in cognitive strategies reduces eating and improves food choice

Abstract: Obesity rates continue to rise alarmingly, with dire health implications. One contributing factor is that individuals frequently forgo healthy foods in favor of inexpensive, high-calorie, unhealthy foods. One important mechanism underlying these choices is food craving: Craving increases with exposure to unhealthy foods (and food cues, such as advertisements) and prospectively predicts eating and weight. Prior work has shown that cognitive regulation strategies that emphasize the negative consequences of unhea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(87 citation statements)
references
References 58 publications
8
73
0
Order By: Relevance
“…Therefore, it is plausible that these populations may have markedly disparate responses to such strategies, both behaviorally and neurally. Previous work has not found any moderating effects of BMI in use of various cognitive strategies ; however, further work in larger samples with a range in BMI, weight‐loss history, and dieting status is needed.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, it is plausible that these populations may have markedly disparate responses to such strategies, both behaviorally and neurally. Previous work has not found any moderating effects of BMI in use of various cognitive strategies ; however, further work in larger samples with a range in BMI, weight‐loss history, and dieting status is needed.…”
Section: Discussionmentioning
confidence: 91%
“…For the food intake meta‐analysis, 43 studies were included with 54 comparisons of effects, leading to a total of 1565 participants in active intervention conditions and 1570 control participants, plus 86 participants undergoing both conditions in a crossover design. Thirteen comparisons were categorized to the intervention category cue exposure (n = 6 in vivo and n = 7 in sensu) and 12 to cognitive regulation strategies (n = 3 acceptance, n = 7 reappraisal, and n = 2 distraction), and 29 comparisons were assigned to cognitive control training (n = 16 ICT, n = 5 AAT, and n = 8 ABM). No studies were found measuring food intake after neurofeedback or biofeedback training.…”
Section: Resultsmentioning
confidence: 99%
“…Of the controlled studies, six ESs were categorized to vivo cue exposure, 39 studies to cognitive regulation strategies (n = 6 acceptance, n = 13 reappraisal, n = 7 suppression, and n = 13 distraction), 13 studies to cognitive control training (n = 3 ICT, n = 4 AAT, and n = 6 ABM), and six to neurofeedback or biofeedback interventions …”
Section: Resultsmentioning
confidence: 99%
“…Cue-induced food craving is a major driver of unhealthy eating behavior and weight gain (Boswell & Kober, 2016), so we focus on craving regulation as a promising intervention target (Boswell et al, 2018;Stice et al, 2015). Specifically, we focus on cognitive reappraisal, the process of reframing a stimulus to change its affective meaning (Gross, 1998).…”
Section: Introductionmentioning
confidence: 99%